The Students’ Anxiety Experience in English Speaking: Causes and Solutions - Sulistyowati, Titis; Utomo, Slamet (Applied Research on English Education (AREE), 2024)
The aims of this research were to find out the speaking anxiety level of Fourth-semester and Sixth-semester students of English Education Department at Universitas Muria Kudus. The research design of this study is quantitative research. The sample of this study were 70 students of fourth and sixth-semester students of English Education Department. The results of the study stated that: A moderate anxiety level was the highest among fourth and sixth-semester students, with 89% with a frequency of 62 students and the moderate anxiety level of fourth-semester students was higher than sixth-semester students with a percentage of 93%. The result of t-calculation indicates that the Sig. (2-tailed) is 0.355 while the Sig. α is 0.05. In this case, the Sig. α is lower than Sig. (2-tailed) (0.355> 0.05). This result means there is no significant difference in anxiety levels between fourth- and sixth-semester students of the English Education Department. The study concludes that the students’ grade does not significantly influence students speaking anxiety.